ASSESSMENT OF GROWTH AND SURVIVAL RATE OF CYPRINUS CARPIO USING AQUAPONICS TECHNOLOGY - AMBREEN , S; ALYAS , S; AHMAD, S; RAFIQUE, HM; GUL, A (Biological and Clinical Sciences Research Journal, 2024)
Aquaponics is an integrated system that combines hydroponics and aquaculture, enabling the cultivation of plants and fish together. It is increasingly popular in non-traditional agricultural settings such as warehouses and marginal soils, as it allows for local food production without synthetic pesticides, chemical fertilizers, or antibiotics. Objective: The study aimed to utilize fish waste and surplus feed as fertilizers for plant growth, producing multiple food products within a single production unit while optimizing space usage. Methods: A 90-day experimental study was conducted from March to May 2022 at the Fish Biodiversity Hatchery Chashma in Mianwali, Punjab, Pakistan. The study involved control and aquaponic treatments, both managed in outdoor tanks. Fifty fingerlings of common carp (Cyprinus carpio) were stocked in each tank. The fish were fed a diet containing 30% crude protein twice daily. The study compared the growth of fish and plants (mint, spinach, tomato) in both treatments. Critical parameters measured included feed conversion ratio (FCR), specific growth rate, and water quality. Statistical analyses were performed using a significance level of p ≤ 0.05. Results: The surplus feed in the aquaponic system facilitated better growth for Cyprinus carpio and plants. The aquaponic system demonstrated a significantly higher growth rate than the control (p ≤ 0.05). The average FCR was 1.86 in the aquaponic system and 2.22 in the control, indicating more efficient feed utilization in the aquaponic setup. Water quality parameters showed no significant differences between the two treatments. Conclusion: The aquaponic system proved to be more effective than the control in improving the growth performance and survival rate of fish and supporting plant growth. This system represents a viable and sustainable alternative for food production, maximizing space utilization and resource efficiency.